(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
This work outlines the historical development stages of obstetrics and gynecology and the influence of bioethical principles on their formation. The study analyzes the progression from ancient medical traditions through the Middle Ages, the modern era, and contemporary medicine. Additionally, it demonstrates the introduction of bioethical norms such as human dignity, safety, consent, privacy, and moral responsibility in medical practices related to reproductive health, and their practical implications. The research substantiates the crucial importance of bioethical approaches in obstetrics and gynecology for medical decision-making, protecting women’s health, and utilizing medical technologies. This work aims to highlight the role and significance of ethical principles in shaping the modern landscape of this medical field.